The characteristics of soil salinization effects on nitrogen mineralization and nitrification in upland fields - Tao, Yinglu; Xie, Wenjun; Xu, Lei; Zhang, Lichang; Wang, Guangmei; Wang, Xiaoning; Shi, Cailing (Frontiers in Environmental Science, 2024)
The influence of soil salinization on nitrogen (N) transformation is largely unknown, which impedes the reasonable management of N in saline fields. A comprehensive meta-analysis was thus conducted to evaluate the effects of salinity and relative soil physicochemical properties on net N mineralization and nitrification in upland soils.Results showed that effects of salinity on the net-N mineralization rate (Min) and nitrification rate (Nit) changed with the salinity level and incubation time. Generally, the inhibitory effect of salt on Min and Nit decreased gradually with incubation time. At 14-16 d of soil incubation, significant stimulatory effects on Min were observed in middle-level (ECe: 12-16 dS m -1 ) and high-level (ECe >16 dS m -1 ) saline soils, and on Nit in low-level (ECe: 4-12 dS m -1 ) saline soils. Regression analysis revealed that the effects of soil organic carbon (SOC), total N (TN), C/N, pH, and clay content on Min and Nit were closely related to salinity levels. Nit at 5-7 d of soil incubation first enhanced and then decreased with C/N increase, and the threshold value was 34.7.The effect of pH on Nit changed with salinity levels, and shifted from stimulation to inhibition with increasing pH. Min at 5-7 d of soil incubation in middle-level group first increased with increasing pH, and decreased when pH was higher than 8.1.Salinization deeply affected soil properties, which further influenced N turnover via alteration of the availability of substrates and microbial biomass and activities. Our findings suggest that the influence of salinity on soil N turnover closely related with salinity level, and salinity level should be considered fully when optimizing N management in saline upland fields.